1996
DOI: 10.1037/0278-7393.22.2.324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lexical frequency and syntactic complexity in spoken-language comprehension: Evidence from the auditory moving-window technique.

Abstract: In 2 experiments, a new technique called the auditory moving window was used to investigate aspects of spoken-language processing. Participants paced their way through spoken sentences divided into word or wordlike segments, and their processing time for each segment was recorded. The 1st experiment demonstrated that high-frequency words in spoken sentences require less time to process than do low-frequency words. The 2nd experiment demonstrated that words in syntactically demanding contexts (i.e., the disambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 61 publications
(97 reference statements)
6
114
3
Order By: Relevance
“…It is noteworthy that a small effect of word frequency was found in our experiments. Ferreira, Henderson, et al (1996) found an effect of word frequency for young adults using single-word segments, while we used multiple-word segments. It is possible that the use of multiple-word segments diluted the effects of word frequency, although the data suggest that this did not occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that a small effect of word frequency was found in our experiments. Ferreira, Henderson, et al (1996) found an effect of word frequency for young adults using single-word segments, while we used multiple-word segments. It is possible that the use of multiple-word segments diluted the effects of word frequency, although the data suggest that this did not occur.…”
Section: Discussionmentioning
confidence: 99%
“…Using this technique, however, Ferreira, Henderson, et al (1996) have shown positive effects for the influence of prosodic information. This suggests that, although pause information might be reduced, presenting spoken language in segments does not appreciably disrupt the perception of intonation, vowel lengthenings, and stress patterns that accompany natural speech (Ferreira, Henderson, et aI., 1996).…”
Section: The Unique Problem Of Spoken Discourse Comprehensionmentioning
confidence: 99%
See 1 more Smart Citation
“…listeners take longer to process low-frequency words relative to high-frequency words (e.g., Ferreira, Henderson, Anes, Weeks, & McFarlane, 1996). Thus, if a passage contains a number of low-frequency words, this may impose additional demands on L2 listeners' working memory as they attempt to recognize the low frequency word (i.e., access the lexicon).…”
Section: Infrequent Wordsmentioning
confidence: 99%
“…Waters and Caplan (1996, 1997) have directly examined the hypothesis that working memory limitations affect older adults' ability to process complex sentences. These studies have used the auditory moving windows paradigm (Ferreira, Henderson, Anes, Weeks, & McFarlane, 1996). This technique allows the listener to start and stop the presentation of sentence and permits the analysis of phrase-by-phrase listening times, analogous to visual moving windows paradigms which permit the analysis of word-by-word or phrase-by-phrase reading times.…”
mentioning
confidence: 99%